Investigation of the Perceived Coaching Behavior and Competency: A Viewpoint of Female Karate Players in Pakistan - Shahida; Jabeen, Afshan; Arif, Taleem; Gul, Tehreem (Regional Lens, 2025)
This study investigated how female karate players in Pakistan perceived coaching behavior and competency, focusing on how these perceptions influenced goal setting and mental readiness. The research highlighted the critical role of coaching quality in shaping athlete development, especially in culturally sensitive, male dominated sports environments. A quantitative, cross sectional design was used. Data were collected via structured questionnaires. The study confirmed that coaching behavior and competency significantly influenced female karate athletes’ goal setting and mental readiness in Pakistan, leading to improved performance. Coaches who provided motivational support, clear guidance, and individualized feedback were perceived as more competent, leading to improved psychological preparedness and performance of the players. These findings reinforced the relevance of leadership and motivation theories within female martial arts contexts. The study highlights the need for gender sensitive coaching training, increased inclusion of female coaches, and the integration of psychological support strategies for the players. It also suggests recruiting and training more female coaches, implementing athlete feedback systems, adopting holistic coaching strategies, and developing supportive policies to foster a safe and empowering environment for female karate players in Pakistan